Efficiency Level Of Zakat Management In Palopo City - Muhammad Ilyas; Ema Sari; Fitriana Umar (UNIVED Press, 2024)
This research aims to evaluate the level of efficiency in zakat management in the city of Palopo. Zakat is one of the fundamental pillars of Islam, designed to distribute wealth to those who are entitled to receive it. Efficiency in zakat management is crucial to ensure that the collected funds are used as efficiently as possible to support those in need. The research methodology involves the analysis of secondary data related to the collection, distribution, and management of zakat funds in the city of Palopo. These data will be analyzed to assess the extent to which zakat management in Palopo achieves the desired level of efficiency. The results of this research are expected to provide valuable insights into the efficiency of zakat management in Palopo and serve as a basis for improvements in zakat collection and distribution. This research can also serve as a guide for zakat institutions and local governments in their efforts to enhance efficiency and effectiveness in zakat management, ultimately improving the well-being of those entitled to receive zakat.